Análise da cultura voltada à inovação em organizações rumo à excelência na região de Santa Maria - RS - Beltrame, Thiago Favarini (2014)
The competitive environment grows more and more. This puts some pressure on organizations to present something more than just trading products and services. Then, it appears the innovation as a key factor for differentiation. This study aims to make an analysis of the culture focused on management innovation in organizations in search of excellence. The population consists of organizations that won the Gaucho Program of Quality and Productivity awards (PGQP) in Santa Maria (RS) and that have a system of asset management based on criteria of excellence. This work include some literature of the area and, after, an exploratory research through the application of a questionnaire which consisted of opened and closed questions. The research showed that the majority of organizations identified the importance of innovation in the organizational environment; however, there is often a lack of funds for investment. It was verified that leadership encourages, in most cases, the development of creative ideas and it provides a supportive environment for it. The cost was identified as the main problem when innovating and it is also noticed that there are few investments in research and development (P&D) of product or service, mainly due to the delay of return. Finally, it was found that most organizations recognize the development of talents and entrepreneurial ideas. It is concluded that organizations identify how innovation is important and that a management innovation would provide a competitive advantage and increase quality and productivity, essential for survival of organizations.